2007
DOI: 10.1007/s11243-007-0266-7
|View full text |Cite
|
Sign up to set email alerts
|

Mixed ligand complexes of FeIII containing pseudohalides, nitrosyl and some mannich bases

Abstract: Reactions of Pentapseudohalonitrosyl ferrate(II) with Morpholinobenzyl benzamide(MBB) and Piperidinobenzyl benzamide(PBB) formed complexes of the type, [Fe(X) 3 (NO)(L-L)] where X = CN ) , NCO ) and N 3 ) and L-L = Morpholinobenzyl benzamide(MBB) and Piperidinobenzyl benzamide(PBB). These compounds have been characterized by various physico-chemical techniques such as elemental analysis, molar conductance, magnetic susceptibility measurements, i.r., electronic spectra, thermal gravimetric analysis. The molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The value of β(0.62) signifies a fair a mount of covaleat character in metal to nitrogen and sulfer bonds. While the value of (10Dq) to be (3769.2)cm -1 , one should expect aband due the transition 4 A2→ 4 T2(F) in the infrared region at (3749)cm -1 , which couldn , t to be observed in the spectrum of the cobalt (II) complex (11) . Conductivity in DMF showed that the complex was non ionic, Table (3). S3: The electronic spectrum of nickel (II) complex exhibits two main absorption band, Table (3) which are assigned to the two transition 1 A1g→ 1 A2g and 1 A1g→ 1 Eg respectively in the a square-planer geometry (25,28) .…”
Section: -Some New Bands Of Weak Intensitymentioning
confidence: 90%
See 1 more Smart Citation
“…The value of β(0.62) signifies a fair a mount of covaleat character in metal to nitrogen and sulfer bonds. While the value of (10Dq) to be (3769.2)cm -1 , one should expect aband due the transition 4 A2→ 4 T2(F) in the infrared region at (3749)cm -1 , which couldn , t to be observed in the spectrum of the cobalt (II) complex (11) . Conductivity in DMF showed that the complex was non ionic, Table (3). S3: The electronic spectrum of nickel (II) complex exhibits two main absorption band, Table (3) which are assigned to the two transition 1 A1g→ 1 A2g and 1 A1g→ 1 Eg respectively in the a square-planer geometry (25,28) .…”
Section: -Some New Bands Of Weak Intensitymentioning
confidence: 90%
“…The synthesis and characterization of the mannich bases derived from heterocyclic rings and different aliphatic amines were described along with a number of their transition metal complexes (9,10) . Mixed ligand complexes of mannich bases play an important role in biological system (11,12) . In the present paper describes the preparation of a new mannich base , in attempt to introduce the amino methyl moiety in the structure mercapto benzothiazole ring which is known to passes a therapeutical applications, as well as to investigate the coordination behavior of the new derivative toward number transition metal ions by preparing mono and mixed ligand complexes and to compare the biological activity of the mannich base and their mono and mixed ligand complexes with the main ring structure.…”
Section: Introductionmentioning
confidence: 99%